Seasonal changes in diel haul‐out patterns of a lacustrine ringed seal (Pusa hispida saimensis) - Niemi, Marja; Nykänen, Milaja; Biard, Vincent; Kunnasranta, Mervi
Seasonal changes in diel haul-out patterns of the lacustrine Saimaa ringed seal (Pusa hispida saimensis) were studied using a combination of satellite telemetry and camera traps during 2007–2015. We found the haul-out activity patterns to vary seasonally. Our results show that during the ice-covered winter period before the seals start their annual molt, the peak in haul-out generally occurs at midnight. Similarly, during the postmolt season of summer and autumn when the lake is free of ice, the haul-out is concentrated in the early hours of the morning. In contrast, over the spring molting period, Saimaa ringed seals tend to haul out around the clock. The spring molt is also the only period when a slight difference in haul-out behavior between the sexes is observed, with females having a haul-out peak at nighttime while the males have a less visible diel pattern. According to our results, the diel haul-out patterns of Saimaa ringed seals are similar to the ones of marine ringed seals. Gathering information on haul-out activity is important in order to safeguard the natural patterns of Saimaa ringed seals in areas that are prone to disturbance from human activities. 2023